2014
DOI: 10.1063/1.4895899
|View full text |Cite
|
Sign up to set email alerts
|

Modeling, measurement, and 3-D equilibrium reconstruction of the bootstrap current in the Helically Symmetric Experiment

Abstract: The bootstrap current for three electron cyclotron resonance heated plasma scenarios in a quasihelically symmetric stellarator (the Helically Symmetric Experiment) are analyzed and compared to a neoclassical transport code PENTA. The three conditions correspond to 50 kW input power with a resonance that is off-axis, 50 kW on-axis heating and 100 kW on-axis heating. When the heating location was moved from off-axis to on-axis with 50 kW heating power, the stored energy and the extrapolated steady-state current … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
10
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 30 publications
4
10
0
Order By: Relevance
“…2001), smaller Pfrisch–Schlüter (Boozer 1981; Schmitt, Talmadge & Anderson 2013) and bootstrap currents (Boozer & Gardner 1990; Schmitt et al. 2014) and reduced Shafranov shift compared to an equivalent sized tokamak for the same parameters. This is quantified by the ‘effective’ rotational transform , where is the periodicity of the stellarator.…”
Section: Performance Evaluationmentioning
confidence: 99%
See 1 more Smart Citation
“…2001), smaller Pfrisch–Schlüter (Boozer 1981; Schmitt, Talmadge & Anderson 2013) and bootstrap currents (Boozer & Gardner 1990; Schmitt et al. 2014) and reduced Shafranov shift compared to an equivalent sized tokamak for the same parameters. This is quantified by the ‘effective’ rotational transform , where is the periodicity of the stellarator.…”
Section: Performance Evaluationmentioning
confidence: 99%
“…The MHD properties of quasi-helical stellarators (Nührenberg & Zille 1988) are somewhat distinct from those of other classes of optimized stellarators. The relatively reduced connection length (the distance along the field line between B max and B min ) implies that quasi-helical stellarators have reduced banana widths, reduced orbit drifts for passing particles (Talmadge et al 2001), smaller Pfrisch-Schlüter (Boozer 1981;Schmitt, Talmadge & Anderson 2013) and bootstrap currents (Boozer & Gardner 1990;Schmitt et al 2014) and reduced Shafranov shift compared to an equivalent sized tokamak for the same parameters. This is quantified by the 'effective' rotational transform ι eff = (ι − N), where N is the periodicity of the stellarator.…”
Section: Magnetohydrodynamic Stabilitymentioning
confidence: 99%
“…It was also shown in HSX that the bootstrap current is in good agreement with a neoclassical calculation [14]. V3FIT was applied to the RFX-mod to demonstrate that a single helicity state in an RFP can be detected using a combination of magnetic and kinetic diagnostics [15].…”
Section: Introductionmentioning
confidence: 89%
“…Because the bootstrap current is strongly dependent on the density and temperature gradient, the possible current profiles, given by equation (5) and (6), encompass a range of profiles that are compatible with the density and temperature derivative. To encompass current density profiles that are not unidirectional, for example when local regions of the bootstrap current density are in the opposite direction or in the current evolution phase when shielding currents exist [14], additional free parameters may be required.…”
Section: Plasma Equilibrium Characterizationmentioning
confidence: 99%
“…Critical to the proper operation of the island divertor in W7-X is control of the edge rotational transform as the bootstrap current evolves. On HSX 3D equilibrium reconstruction was used to obtain the bootstrap current profile and to demonstrate the critical role of the radial electric field on that profile [10]. Finally, it was demonstrated that optimization of the position of magnetic diagnostics used to perform the reconstruction can reduce the uncertainty in the plasma pressure and current profiles [11].…”
Section: Configuration Optimizationmentioning
confidence: 99%